2013
DOI: 10.1590/0103-6440201302266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Microbial Colonization of the Oral Cavity in Newborns

Abstract: The host defense mechanisms are not well developed in neonates. The aim of this study was to evaluate the dynamics of microbial colonization of the oral cavity in newborns. Eighty-one samples of the oral microbiota were obtained from 51 healthy newborns 10 min to 53 h after birth by gently rubbing sterile swabs onto the surface of the tongue, cheek mucosa, alveolar process and palate. After microbiological processing, counting of the colony forming units of streptococci, staphylococci and Gram-negative aerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 24 publications
(33 reference statements)
1
47
1
8
Order By: Relevance
“…First, we found 20 kinds of oral flora, the most frequent of which were Streptococcus , MRSA, and CNS. An earlier study also found Staphylococcus and Streptococcus to be major flora in the oral mucus of healthy newborns, as early as 10 min to 53 hr after birth (Nelson‐Filho et al, ). Despite the lack of research on oral flora in high‐risk newborns, including infants born prematurely, our findings suggest the similarity of oral flora types in newborns regardless of their clinical characteristics during early postnatal period.…”
Section: Discussionmentioning
confidence: 89%
“…First, we found 20 kinds of oral flora, the most frequent of which were Streptococcus , MRSA, and CNS. An earlier study also found Staphylococcus and Streptococcus to be major flora in the oral mucus of healthy newborns, as early as 10 min to 53 hr after birth (Nelson‐Filho et al, ). Despite the lack of research on oral flora in high‐risk newborns, including infants born prematurely, our findings suggest the similarity of oral flora types in newborns regardless of their clinical characteristics during early postnatal period.…”
Section: Discussionmentioning
confidence: 89%
“…The oral environment is sterile at birth, but the introduction of microorganisms can occur during labor, through microbial invasion of amniotic cavity and aspiration of contaminated amniotic fluid, or by contact with microorganisms present in the birth canal or genital secretions or maternal feces (9,18,19). Thus, the oral cavity can harbor various microbial species, including microorganisms of the Enterobacteriaceae and Pseudomonadaceae multiresistant families.…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms can survive in the environment and also temporarily on the hands of persons handling newborns, making the child-child transmission easier. Another important risk factor for NB infections is the limited protection of the immune system during this period of life (8,9). These and other pathogenic microorganisms may remain viable in areas associated and non-associated with the newborn, increasing the risk of infection outbreaks (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago it was shown that the mouth microbiota evolves with age. Colonization begins at birth (Prince et al 2014) when dynamic microbial colonization of the oral cavity begins (Nelson-Filho et al 2013). The profile of the predominant phylum evolves during childhood and youth and has almost stabilized by adulthood (Human Microbiome Project Consortium 2012).…”
Section: Agingmentioning
confidence: 99%